2023
DOI: 10.1017/jfm.2023.488
|View full text |Cite
|
Sign up to set email alerts
|

A nematic liquid crystal with an immersed body: equilibrium, stress and paradox

Abstract: We examine the equilibrium configurations of a nematic liquid crystal with an immersed body in two dimensions. A complex variables formulation provides a means for finding analytical solutions in the case of strong anchoring. Local tractions, forces and torques on the body are discussed in a general setting. For weak (finite) anchoring strengths, an effective boundary technique is proposed which is used to determine asymptotic solutions. The energy-minimizing locations of topological defects on the body surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 89 publications
0
0
0
Order By: Relevance
“…The existing studies [14,24] also showed the defects preferred to be located around the sharp corners, which is consistent with the present simulations. To further investigate the effects of sharp corners on the defect positions, it would be suitable to use Schwartz-Christoffel maps in the same way as the existing studies [14,24]. However, it is practically difficult to compute the energy numerically due to the existence of singularities on the integration path coming from the conformal map.…”
Section: (Ii) Anisotropic Domains With Cornerssupporting
confidence: 93%
See 4 more Smart Citations
“…The existing studies [14,24] also showed the defects preferred to be located around the sharp corners, which is consistent with the present simulations. To further investigate the effects of sharp corners on the defect positions, it would be suitable to use Schwartz-Christoffel maps in the same way as the existing studies [14,24]. However, it is practically difficult to compute the energy numerically due to the existence of singularities on the integration path coming from the conformal map.…”
Section: (Ii) Anisotropic Domains With Cornerssupporting
confidence: 93%
“…According to our simulations, the defects tended to be located around rounded corners after the energy-minimizing procedure. The existing studies [14,24] also showed the defects preferred to be located around the sharp corners, which is consistent with the present simulations. To further investigate the effects of sharp corners on the defect positions, it would be suitable to use Schwartz-Christoffel maps in the same way as the existing studies [14,24].…”
Section: (Ii) Anisotropic Domains With Cornerssupporting
confidence: 93%
See 3 more Smart Citations